Improvement of uneven charge distribution on piezoelectric circular diaphragm with notched-substrate - Yu Han; Yuanbo Li; Yangyiwei Yang; Minghao Li; Tongqing Yang (AIP Advances, 2020)
Vibration-based energy harvesting using piezoelectric circular diaphragms (PCDs) has drawn much attention in recent decades because of their compatibility with various operation modes. However, it has been revealed that their output distribution over the electrode surface is highly uneven, with less output generated around the edge. In this work, we present a possible structure of a PCD, which consists of a notched substrate (notched PCD), a PZT-5H disk, and an annular mass, in which the charge output around the edge of the PCD can be enhanced. Moreover, the difference in charge production between the outer region (the region with less charge) and the inner region (the region with high charge) is reduced so that the output distribution of the PCD is improved. In the notched-PCD, the perimeter region of the PCD is better utilized, which leads to a higher output power. Finite element analysis is performed in order to provide further information about how the notched substrates affect the output distribution on the PCD: the more the notches on the substrate, the more the extra charge generated on the PZT-5H disk. The experimental results also present the increases in the total output power of the notched PCD compared to the PCD without notches. In addition, there are two peaks in the normalized output power curve, the values of which are 1.6 corresponding to 9 mW for the output (with 10-notched PCD) and 1.8 corresponding to 10 mW for the output (with 4-notched PCD).